Magnetic properties in YBa2Cu3O7 single crystals with a crossed configuration of columnar defects - Shim, SY; Kim, DH; Hwang, JS; Hwang, TJ; Lim, HR; Oh, SJ; Ri, HC; Park, JH; Hahn, TS; Kim, JT (KOREAN PHYSICAL SOC, 1998)
We have studied the magnetic properties of YBa2CU3O7 Single crystals with crossed columnar defects of various splay angles (0 degrees similar to +/-40 degrees). In the temperature range between 50 and 70 K, crystals with +/-20 degrees show the highest enhancement in J(c) near the matching field of the defect density. We also find that the normalized creep rates and the vortex, activation energies change with the splay angle. The relaxation rate for a +/-20 degrees crystal shows the lowest value for magnetic fields near the matching field, consistent with the J(c) results. Possible vortex dynamics associated with the crossed columnar defects are discussed.